Visualizing power negation in Sitio Kahusayan through social realist digital graphics and community art - Senarillos, Kenneth Paul P. (2018)
Arturo Danto (1964) defines ?art? as an ascription of the people in the artworld. In this institutional context, artworks gain position and prestige. These artworks are product of the imagination of the individual geniuses. They are the experts entrusted by society with the task of classifying and explaining art. According to Kate Crehan (2011), these individuals are the ones that set the standards of what constitute a good art. This artworld-elitism has been criticized by the progressive artists of the mid-2oth century. During the 1960?s, visual artists wanted to dissimilate from the elitist notion of art that is solely done by the ?genius? artist and judged by the standards imposed by the art world?s curators. Findings new ways to do art was the driving force of this era?s artistic movement. The artists? search for an alternative art-making process took different forms but all of them had the same core of taking art to the ordinary people; thus, the emergence of community art. This production thesis aims to create social realist digital art illustrations based from the lifeworld narratives and collaboration of the Sitio Kahusayan community. The study employs Andy Parkinson and Jamie Buttrick?s (2017) cultural co-design model and Johan Galtung?s theory of power negation: the self-respect, self-reliance, and fearlessness of the participants. Through the model and theory, the participants? local voices and works will shape the meaning and output of the project.